New frontiers in peritoneal malignancies - Canbay, Emel (Chinese Journal of Cancer Research, 2013)
I was honored to be asked to write an editorial on ‘cytoreductive surgery using peritonectomy and visceral resections for peritoneal surface malignancy’ (1) written by Paul H. Sugarbaker. A strategic approach using peritonectomy and cytoreductive surgery to treat peritoneal cancers has gradually evolved over the past 30 years that has emanated by our impressive leader Paul H. Sugarbaker. He has brought many surgeons together from all over the world for these procedures. His skill made so many of us enthused by peritonectomy procedures and cytoreductive surgery with long operation time, a major postoperative morbidity and high mortality risk. However, we are all persisted with these procedures because of sometimes moribund patients with peritoneal cancers may cure with peritonectomy procedures and cytoreductive surgery.